ENGLISH LANGUAGE LEARNING METHOD IN PRESCHOOL EDUCATION - Shamsuddinova Diyoraxon Yorqinbek qizi; Qurbonova Namuna Umidjon qizi (TADQIQOTLAR, 2025)
Annotation:  This  article  examines  the  most  effective  methods  for  teaching English to preschool children. It highlights how early language exposure fosters long-term proficiency and discusses pedagogical strategies including play-based learning, Total Physical Response (TPR), storytelling, and the use of songs and rhymes. The article  also  emphasizes  the  importance  of  a  rich,  immersive  environment  and  age-appropriate materials to encourage natural language acquisition among young learners.